2021
DOI: 10.1111/jopr.13370
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Guiding Sleeve Design on Intraosseous Heat Generation During Implant Site Preparation (In Vitro Study)

Abstract: Purpose To compare the effect of different designs of guiding sleeves on heat generation during implant surgery while using different cooling fluid temperatures. Material and Methods Temperature measurements were performed during guided implant site preparation in bovine rib samples using two K‐ type thermocouples at 2 mm and 8 mm depths. Three groups were tested according to guiding sleeve design: conventional cylindrical sleeve, open C‐shaped sleeve, and modified cylindrical sleeve. Each group was irrigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Cooling efficiency may be further decreased with the use of navigation guides. To overcome this negative effect, a gap between the drill guide sleeve and the gingiva is often maintained during the fabrication of dental implant surgical guides to ensure the access of the coolant to the drill [ 5 ]. However, due to the flexibility of narrower and longer drills used in endodontics, this is rarely possible during navigated endodontic drilling.…”
Section: Introductionmentioning
confidence: 99%
“…Cooling efficiency may be further decreased with the use of navigation guides. To overcome this negative effect, a gap between the drill guide sleeve and the gingiva is often maintained during the fabrication of dental implant surgical guides to ensure the access of the coolant to the drill [ 5 ]. However, due to the flexibility of narrower and longer drills used in endodontics, this is rarely possible during navigated endodontic drilling.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that greater damage occurred when heat at 53°C was generated for 1 minute [ 8 ]. Permanent cessation of blood flow at temperatures above 60°C has been proven to cause necrosis of the bone [ 9 ]. In previous studies, the use of a surgical guide led to higher heat generation; however, the highest recorded temperature was below the bone necrosis threshold [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various efforts have been made to achieve effective irrigation while using a surgical guide, including modification of the sleeve design. In a study on heat generation according to the sleeve design (cylindrical, open C-shaped, and modified cylindrical), the open C-shaped and modified cylindrical sleeves showed better drill diameters and measurement depths and led to a significantly lower temperature increase regardless of the irrigation temperature [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the drilling technique for the implant bed preparation, parameters such as thrust force, feed rate, irrigation, drilling speed, and operator experience have been investigated [12][13][14][15][16][17][18]. Thrust force and feed rate are influenced by the operator, and it seems that novices produce higher forces and feed rates compared to experts, resulting in higher temperatures during bone drilling [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Irrigation is essential for controlling the temperature during high-speed drilling. Specifically, external irrigation is more efficient for cooling than internal irrigation; high volumes of irrigation reduce the temperature more than low volumes of irrigation [14]; and reduced coolant temperature controls the thermal increase better than higher coolant temperatures [15,16]. If the coolant cannot reach the targets (drill surface and bone), the temperature elevation is not controlled.…”
Section: Introductionmentioning
confidence: 99%